Strategi Promosi Program Radio BSP 103.8 FM dan Tiara 99.8 FM Pekalongan dalam Meraih Jumlah Pemasang Iklan 2012 - Indra Muvti (Jurusan Ilmu Komunikasi, 2013)
This research aimed to describe the promotion strategic of BSP 103.8 FM and Tiara 99.8 FM radio to reach the amount of advertiser. The formulation of the problem on the research was how does the promotion strategic of BSP 103.8 FM and Tiara 99.8 FM radio to reach the amount of advertiser?. Bahurekso Suara Pekalongan (BSP) is a public radio at Pekalongan on Bahurekso Suara Pekalongan, used 103.8 FM. The mission of it are built a positive trend at Pekalongan and born 1991. The corporate name Tiara FM is Smart Swara. The reseach used qualitative method. The object on the reseach was marketing communicaton strategic which is used by BSP 103.8 FM and Tiara 99.8 FM radio from Pekalongan to reach the amount of advertiser. The instruments used to collect data in this research were interview and documentation. The technique used to analyze data has been collected was analitical descriptive, using qualitative analyze. The result of the research shows that the BSP 103.8 FM radio used STPD strategic to establish some variables on marketing program planning, follow as: 1) The BSP 103.8 FM radio from Pekalongan chose the segmentation based of geographic, demographic, and psychological segmentation; 2) The BSP 103.8 FM and Tiara 99.8 FM radio from Pekalongan established the target based of the segmentation which is available; 3) According to BSP 103.8 FM radio, positioning gave attention to the program characteristic, price, function, user, and based on the problem of customer. Tiara 99.8 FM radio gave attention to the program characteristic and price only. 4) The BSP 103.8 FM radio used differentiation strategic to complete marketing activity by showing differences a program or service to the competitor specifically. The differentiation has been used by BSP 103.8 FM radio were the differentiation of a program, customer service, personal, channel, and image. While Tiara 99.8 FM radio used the differentiation of customer service and personal only as its differentiation strategic.